Diagnostic value of ultrasound in nodular thyroid lesions - Rubén González Tabares; Olayma Fernández Cedeño; Libardo Castillo Lamas (Revista Cubana de Medicina Militar, 2021)
Introduction: The risk of malignancy of a thyroid nodule can be stratified from ultrasound signs. Various systems have been used for this purpose, although without consensus on which to use. Objective: To evaluate the diagnostic utility, for nodular disease, of the ultrasound signs, as well as of four systems of stratification of the risk of malignancy. Methods: A prospective study was conducted that included 151 thyroid nodules. Thyroid ultrasound identified composition, echogenicity, shape, margins and echogenic foci. The risk of malignancy of each nodule was estimated according to four stratification systems. They were diagnosed benign or malignant according to cytological study, surgery, or a minimum follow-up of two years. The relationship between the clinical characteristics was identified, as well as the risk stratification systems and the chi-square diagnosis. Sensitivity, specificity, positive predictive value, negative predictive value and diagnostic precision of each ultrasound sign were calculated. Results: A relationship was found between family history and physical examination with the diagnosis of malignancy. The best diagnostic precision corresponded to cystic composition (90.0%), anechoic (90.1%), irregular margins (95.4%) and peripheral calcifications (92.7%). All the ultrasound risk stratification systems for malignancy were able to adequately discriminate between malignant and benign lesions (p<0.05). Conclusions: The highest risk of malignancy was presented by solid, hypoechoic nodules, with irregular margins and with microcalcifications. All four malignancy risk stratification systems are adequate, although the American College of Radiology is more accurate.